The impact of trade and trade policy on the environment and the climate: A review - Gabriel Felbermayr; Sonja Peterson; Joschka Wanner (Austrian Institute of Economic Research (WIFO), 2022)
While international trade can offer gains from specialisation and access to a wider range of products, it is also closely interlinked with global environmental problems, above all, anthropogenic climate change. This survey provides a structured overview of the economic literature on the interaction between environmental outcomes, trade, environmental policy and trade policy. In this endeavour, it covers approaches reaching from descriptive data analysis based on Input-Output tables, over quantitative trade models and econometric studies to game-theoretic analyses. Addressed issues are in particular the emission content of trade and emissions along value chains, the relocation of dirty firms and environmental impacts abroad, impacts of specific trade polices (such as trade agreements or tariffs) or environmental policy (such as Border Carbon Adjustment), transportation emissions, as well as the role of firms. Across the different topics covered, the paper also tries to identify avenues for future research, with a particular focus on extending quantitative trade and environment models.
Keywords: 330